Perfil de Selênio e Zinco em gestantes saudáveis - Vianna, Cláudia Michielin Della Colleta [UNESP] (2016)
Objective: To evaluate the profile of total selenium and zinc in eutrophic, overweight and obese women. Methodology: A cross-sectional study was carried out in 126 either gestational period women, being them either eutrophic or obese pregnant women. Biochemical markers were assessed: total zinc and selenium, in addition to anthropometric measurements and food intake. Participants will be divided according to body mass index, the control group (CG) of: 42 eutrophic pregnant participants; group (OG) of: 42 overweight pregnant women; and group (OWG) of: 42 obese pregnant women. Statistical tests for equality between groups, parametric tests and the association between BMI and profile of Se and Zn were performed, considering significant differences the value of p <0.05. Results: There was no significant difference between the three groups regarding the average values of zinc in plasma (CG, 53±7 μg/dl; OWG, 57± 8 µg/dl; OG, 55±6 µg/dl) and selenium plasma (CG, 45±12 µg/L; OWG, 48±12 µg/L, OG, 43±6µ g/L) and there was no significant difference in mean values between the three groups for zinc in the erythrocyte (CG, 11±3 µg/ml; OWG, 10±3 µg/ml; OG, 10±2 µg/ml) and selenium in erythrocytes (CG 64±17µg/L; OWG of 63±17 µg/L; OG 60±13 µg/L). Conclusion: The present study demonstrated the presence of deficiency of the micronutrients zinc and selenium in all groups of pregnant women, with and without overweight and obesity. However, more studies are needed to better understand the consequences of changes in micronutrients in pregnant women and base a possible supplementation.